Force Modulation and Adaptability of 3D‐Bioprinted Biological Actuators Based on Skeletal Muscle Tissue. Issue 2 (13th December 2018) - Mestre, Rafael; Patiño, Tania; Barceló, Xavier; Anand, Shivesh; Pérez‐Jiménez, Ariadna; Sánchez, Samuel
Abstract: The integration of biological systems into robotic devices might provide them with capabilities acquired from natural systems and significantly boost their performance. These abilities include real‐time bio‐sensing, self‐organization, adaptability, or self‐healing. As many muscle‐based bio‐hybrid robots and bio‐actuators arise in the literature, the question of whether these features can live up to their expectations becomes increasingly substantial. Herein, the force generation and adaptability of skeletal‐muscle‐based bio‐actuators undergoing long‐term training protocols are analyzed. The 3D‐bioprinting technique is used to fabricate bio‐actuators that are functional, responsive, and have highly aligned myotubes. The bio‐actuators are 3D‐bioprinted together with two artificial posts, allowing to use it as a force measuring platform. In addition, the force output evolution and dynamic gene expression of the bio‐actuators are studied to evaluate their degree of adaptability according to training protocols of different frequencies and mechanical stiffness, finding that their force generation could be modulated to different requirements. These results shed some light into the fundamental mechanisms behind the adaptability of muscle‐based bio‐actuators and highlight the potential of using 3D bioprinting as a rapid and cost‐effective tool for the fabrication of custom‐designed soft bio‐robots. Abstract : Biological actuators based on skeletal muscle tissue are fabricated via 3D bioprinting in a versatile, cost‐effective, process‐integrated, and rapid manner. 3D‐bioprinted bio‐actuators are shown to adapt after long‐term electrical stimulation. Force output and gene expression analysis are used to evaluate their degree of adaptability after modifying the stimulation frequencies and the stiffness of mechanical constraints.